Fatty acids Omega-3 and Omega-6 in fish nutrition – sources and relations (Revista de Ciências Agroveterinárias, 2007)
There are two series of essential fatty acids, which can not be synthesized by animals or humans and must be supplied in the diet. The n-6 series are derived from linoleic acid (LA) and the n-3 series from alpha linolenic acid (ALN). From these polyunsatured fatty acids (PUFAs) are synthesized the arachidonic acid (AA), eicosapentanoic acid (EPA) and docosahexanoic acid (DHA). Fish are generally good sources of fatty acids, but there are differences between marine and freshwater fishes. Low levels of LA and ALN characterize lipids of marine fish species, as well as high levels of long chain n-3 high-unsaturated fatty acid (HUFA). However, freshwater fishes seem to have greater capacity to desaturate and elongate the fatty acids, synthesized by algi or plants, into EPA and DHA. Fish oil has been utilized for farm fish feeding marine, but it represents a finite resource. With the fishery resource stagnation, the price tends to increase which turns more interesting to search alternative sources. A sustainable source to substitute fish oil in fish feeding includes vegetable oils like rapeseed oil and linseed oil. Research has been carried out to find the best ratio n-3/n-6 in fish muscle. This finding is important to increase fish nutritional value for human health, since the highly unsaturated fatty acids provide various benefits, such as preventing heart diseases, and an increase of their consume should be stimulated.
Keywords: EPA; DHA; lipid; vegetable oil; health.